1967
DOI: 10.1002/zaac.19673520513
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen an Selen‐Sauerstoff‐Verbindungen. XLII. Dimethyl‐ und Diäthylselenoxid sowie ihre Oxoniumsalze Darstellung, Eigenschaften und Schwingungsspektren

Abstract: (CH3)2SeO und (C2H5)2SeO werden aus R2SeBr2 mit Ag2O in CH3OH dargestellt. Bei der Oxydation von R2Se mit NO2 erhält man die Addukte R2SeO · N2O4. Das Studium der thermischen Zersetzung der Methylverbindung ergibt (CH3)2SeO · N2O4 → CH3SeO · OH + CH2O + 2 NO. Nach Molmassebestimmungen, RAMAN‐ und IR‐Spektren liegen in wäßriger Lösung keine Dihydroxide R2Se(OH)2, sondern monomere R2SeO‐Molekeln mit H‐brückengebundenen H2O‐Molekeln in dem pH‐abhängigen Gleichgewicht R2SeO …︁ HOH ⇄ [R2SeOH]+ + OH− vor. Aus äquimo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

1967
1967
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 28 publications
2
11
0
1
Order By: Relevance
“…Indeed, the bands in the 570-600 cm À1 region are present only in the SeMet geodin crystal and not in the spectra of the mother liquor or in the wild-type geodin crystal (Table 2). This spectral feature can be confidently assigned to the C-Se stretching, in agreement with previous Raman studies on selenium-containing organic compounds (Hamada & Morishita, 1977;Paetzold et al, 1967) and on the amino acid selenomethionine (Zainal & Wolf, 1995;Lopez et al, 1981).…”
Section: Raman Microscopysupporting
confidence: 91%
“…Indeed, the bands in the 570-600 cm À1 region are present only in the SeMet geodin crystal and not in the spectra of the mother liquor or in the wild-type geodin crystal (Table 2). This spectral feature can be confidently assigned to the C-Se stretching, in agreement with previous Raman studies on selenium-containing organic compounds (Hamada & Morishita, 1977;Paetzold et al, 1967) and on the amino acid selenomethionine (Zainal & Wolf, 1995;Lopez et al, 1981).…”
Section: Raman Microscopysupporting
confidence: 91%
“…Alternatively, upon deprotonation of O B , the selenurane in B1 P may decompose by B1 TS to the seleninic acid (1 R ) if the proton is passed to O 1 (the reverse of step B1), but the activation barrier for this process is 3.5 kcal/ mol higher than AB TS . These results are consistent with the assignment of the intermediate as the seleninyl sulfide A by Kice and Lee [20] who noted that selenoxides are known to strongly associate with water, but do not form the hydrate [58]. Whereas our DFT analysis [31] of the oxidation of selenomethionine showed that hydrate formation is highly endothermic (28 kcal/ mol), the DG for interconversion of A and B is much lower (<10 kcal/mol), suggesting that the intermediate may be the selenurane under certain conditions.…”
Section: Interconversion Of a And Bsupporting
confidence: 92%
“…Diselenoethers, particularly compound 12, gave poor or no yield unless alkylation was performed at low temperatures (À20 to À25°C). This can be attributed to the formation of an unstable episelenonium ion [19] intermediate, which eliminates a molecule of ethylene to regenerate the starting diselenide. Only moderate yields were obtained for unsymmetrical tellurides.…”
Section: Resultsmentioning
confidence: 97%